The attitude towards other species in biodesign: an analysis of different frameworks - Strobel do Nascimento, Elisa; Heemann, Adriano (Pensamentos em Design, 2024)
Biodesign refers to, among other things, the design with other living organisms and systems. This paper aims to reflect upon and discuss humans’ relationships with other species in biodesign - drawing on the analysis of existing frameworks that organise it. The questions that drive the discussion are: (I) What are the biodesign organising frameworks? and (II) What do these frameworks say about how humans relate to other species in biodesign? Seven frameworks were analysed, resulting from systematic and narrative literature reviews. The analysis reveals different attitudes towards other species. We argue that biodesign might not be a collaboration. This is an expanded version of an XI ENSUS 2024 conference paper.